The sweetest heist in history - Spencer, Octavia (Spencer, Octavia. Randi Rhodes, ninja detective, 2015)
On a trip to New York City to visit Randi's aunt, the ninja detective trio explores Randi's old neighborhood in Brooklyn, where they uncover an art heist involving Fabergé eggs. Except no one will believe them. So they'll just have to catch the criminals in the act...